Inflammatory pseudotumor of the liver treated by trisegmentectomy: a case report - Perek, Sadık; Erenler, İlknur and Sarıbeyoğlu, Kaya and Özbay, Gülşen (Cerrahpaşa Medical Journal, 2013)
Inflammatory pseudotumor of the liver is a rare benign tumor that can mimic liver neoplasms either on clinicoradiological or pathological examinations. Herein we report a case which was suspected as hepatocellular carcinoma based on imaging findings and was underwent surgery. Histopathologic examination showed xanthogranulomatous inflammation with mononuclear inflammatory cells. The patient remains well during a 1year follow up period.